Teaching audience adaptation using connected presentations and teamwork. Issue 2 (3rd April 2017) - Opt, Susan K.
Abstract : Courses: Introduction to Communication, Public Speaking, Persuasion, Business Communication. Objective: This activity increases students' understanding of audience adaptation and improves their ability to adapt presentations to specific audiences.